Reducing Inequalities in Oral Health in the Africa and Middle East Region. (July 2015) - Sheiham, A.; Williams, D.M.
Dentistry is facing many serious challenges and threats. Addressing them will require major changes in strategy. This work outlines the extent of dental disease in the Africa and Middle East Region (AMER) and suggests strategies to reduce inequalities in oral health. The main oral health challenges in the AMER relate to controlling the relentless increase in caries with age. A very conservative estimate of population caries levels suggests that a 5-fold increase in dental personnel would be required just to treat current levels of caries. Hence, we argue that current approaches to control caries in the AMER are both ineffective and unaffordable, and a new model to promote oral health is needed. Unless determinants of noncommunicable diseases are addressed and access to evidence-based minimal intervention dental care is improved, the burden of dental disease will persist. The new oral health promotion model calls for an integrated intersectoral common risk factor approach, namely, "oral health in all policies" (OHiAP). An OHiAP framework will initiate high-level policy initiatives and intersectoral partnerships. Oral health professionals have an important advocacy role in securing the fundamental changes in health strategy needed to control the growing, unjust, and unaffordable burden of oral disease.